IMPLEMENTATION OF MUDHARABAH CONTRACT ON CIAMIS PRUDENTIAL SHARIA INSURANCE PRODUCTS - Dede Husni Mubarok; Dedeh Hamidah; Mira Nurmayanti (Fakultas Ekonomi dan Bisnis Islam, Institut Agama Islam Darussalam (IAID) Ciamis, Jawa Barat, INDONESIA, 2021)
This research is motivated by the provisions of the DSN-MUI Fatwa Guideline Number 21/DSN-MUI/IV/2001, which states that a mudharabah contract can be converted into a tabarru contract, but a tabarru contract cannot be converted into a mudharabah contract. The purpose of this study was to determine the mudharabah contract in Pru Taqwa Prudential Syari’ah Ciamis insurance. This study also aims to determine the tabarru’ contract on Pru Taqwa Prudential Syari’ah Ciamis insurance, as well as to determine the implementation of the mudharabah and tabarru’ contracts on Pru Taqwa Prudential Syari’ah Ciamis insurance. The type of research used is field qualitative with descriptive analysis method. This study uses primary and secondary data sources. The results show (1) the mudharabah contract at Pru Taqwa Prudential Syari’ah Ciamis, namely where the insurance participant/insured is domiciled as shahibul maal and the Pru Taqwa Prudential Syari’ah company is the mudharib/manager. Where participants leave contributions (premium payments) to companies which will then be managed in the form of investments in halal companies that have been approved by the Indonesian Ulema Council. (2) The tabarru’ contract at Pru Taqwa Prudential Syari’ah Ciamis is a contract that changes the contract where the participant becomes a risk bearer other than the company. The company is only a manager/operator. The manager is not entitled to use the tabarru’ funds if there is no power of attorney from the insurance participant to avoid maisyir, gharar and usury. (3) The implementation of the mudharabah and tabarru’ contracts on Pru Taqwa Prudential Syari’ah Ciamis is in accordance with existing provisions, namely based on the DSN-MUI Fatwa Number 21/DSN-MUI/IV/2001 concerning General Guidelines for Sharia Insurance, namely the mudharabah contract which can be converted into a tabarru’ contract and a tabarru’ contract cannot be converted into a mudharabah contract.